2018
DOI: 10.1002/anie.201805664
|View full text |Cite
|
Sign up to set email alerts
|

Chemodynamic Therapy: Tumour Microenvironment‐Mediated Fenton and Fenton‐like Reactions

Abstract: Tailored to the specific tumour microenvironment, which involves acidity and the overproduction of hydrogen peroxide, advanced nanotechnology has been introduced to generate the hydroxyl radical ( OH) primarily for tumour chemodynamic therapy (CDT) through the Fenton and Fenton-like reactions. Numerous studies have investigated the enhancement of CDT efficiency, primarily the increase in the amount of OH generated. Notably, various strategies based on the Fenton reaction have been employed to enhance OH genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
966
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,579 publications
(969 citation statements)
references
References 73 publications
0
966
0
3
Order By: Relevance
“…Currently, cancer poses an increasing threat to human health . Accordingly, various pre‐clinical studies have demonstrated the usefulness of inorganic nanoparticles .…”
Section: Figurementioning
confidence: 99%
“…Currently, cancer poses an increasing threat to human health . Accordingly, various pre‐clinical studies have demonstrated the usefulness of inorganic nanoparticles .…”
Section: Figurementioning
confidence: 99%
“…The PDT utilities light-activated photosensitizers to convert oxygen (O 2 ) to ROS 13 , whereas CDT takes advantage of an in situ Fenton or Fenton-like reaction between hydrogen peroxide (H 2 O 2 ) and catalysts to generate cytotoxic hydroxyl radical (•OH) 14,15 . Recently, the PDT/CDT combination therapy has been continuously explored to amplify the tumor oxidative stress and achieve better anticancer therapeutic effect than monotherapy [16][17][18][19][20] .…”
mentioning
confidence: 99%
“…Recently, the PDT/CDT combination therapy has been continuously explored to amplify the tumor oxidative stress and achieve better anticancer therapeutic effect than monotherapy [16][17][18][19][20] . However, the TME feature of hypoxia, depletable amount of H 2 O 2 and the glutathione (GSH) depletion effect on ROS still limit ROS efficiency 15,21,22 . Two different feasible strategies have been proposed to relieve hypoxia in PDT and supplement the cellular amount of H 2 O 2 in CDT, respectively, amplifying endogenous O 2 / H 2 O 2 generation 11,[23][24][25][26] or directly delivering exogenous O 2 /H 2 O 2 into cells [27][28][29] .…”
mentioning
confidence: 99%
“…Recently, Fenton catalyst-mediated catalytic nanomedicine has been demonstrated as promising selective cancer therapy that generates toxic hydroxyl radicals specifically in the tumor microenvironment. [86,93,94] It has been well documented that the catalytic capacity of Fenton catalysts determines the reaction rate and production yield, especially given the limited amount of endogenous catalytic reactants (i.e., H 2 O 2 ). However, challenges still remain with regards to developing a Fenton catalyst with high catalytic efficiency to tumors and a concurrent high degree of biocompatibility to normal cells.…”
Section: Selectivity By Endogenous Stimuli-responsementioning
confidence: 99%